The transcription factor ATF4 mediates endoplasmic reticulum stress-related podocyte injury and slit diaphragm defects. - Krausel, V.; Pund, L.; Nüsse, H.; Bachir, H.; Ricker, A.; Klingauf, J.; Weide, T.; Pavenstädt, H.; Krahn, M.P.; Braun, D.A. (Kidney International, 2023)
Mutations in OSGEP and four other genes that encode subunits of the KEOPS complex cause Galloway-Mowat syndrome, a severe, inherited kidney-neurological disease. The complex catalyzes an essential posttranscriptional modification of tRNA and its loss of function induces endoplasmic reticulum (ER) stress. Here, using Drosophila melanogaster garland nephrocytes and cultured human podocytes, we aimed to elucidate the molecular pathogenic mechanisms of KEOPS-related glomerular disease and to test pharmacological inhibition of ER stress-related signaling as a therapeutic principle. We found that ATF4, an ER stress-mediating transcription factor, or its fly orthologue Crc, were upregulated in both fly nephrocytes and human podocytes. Knockdown of Tcs3, a fly orthologue of OSGEP, caused slit diaphragm defects, recapitulating the human kidney phenotype. OSGEP cDNA with mutations found in patients lacked the capacity for rescue. Genetic interaction studies in Tcs3-deficient nephrocytes revealed that Crc mediates not only cell injury, but surprisingly also slit diaphragm defects, and that genetic or pharmacological inhibition of Crc activation attenuates both phenotypes. These findings are conserved in human podocytes where ATF4 inhibition improved the viability of podocytes with OSGEP knockdown, with chemically induced ER stress, and where ATF4 target genes and pro-apoptotic gene clusters are upregulated upon OSGEP knockdown. Thus, our data identify ATF4-mediated signaling as a molecular link among ER stress, slit diaphragm defects, and podocyte injury, and our data suggest that modulation of ATF4 signaling may be a potential therapeutic target for certain podocyte diseases.